2018
DOI: 10.48550/arxiv.1812.00515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing the LSST Observing Strategy for Dark Energy Science: DESC Recommendations for the Wide-Fast-Deep Survey

Abstract: Cosmology is one of the four science pillars of LSST, which promises to be transformative for our understanding of dark energy and dark matter. The LSST Dark Energy Science Collaboration (DESC) has been tasked with deriving constraints on cosmological parameters from LSST data. Each of the cosmological probes for LSST is heavily impacted by the choice of observing strategy. This white paper is written by the LSST DESC Observing Strategy Task Force (OSTF), which represents the entire collaboration, and aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 13 publications
4
43
0
Order By: Relevance
“…The DC2 baseline cadence is sub-optimal with respect to the recent developments in LSST cadence studies Lochner et al 2018Lochner et al , 2021. Repeating this DC2 image simulation and analysis on alternative cadences is impractical from both a computational and human-effort perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The DC2 baseline cadence is sub-optimal with respect to the recent developments in LSST cadence studies Lochner et al 2018Lochner et al , 2021. Repeating this DC2 image simulation and analysis on alternative cadences is impractical from both a computational and human-effort perspective.…”
Section: Discussionmentioning
confidence: 99%
“…This code has been used through the direct use of API in the study of serendipitous discoveries of Kilonovae using the LSST (Setzer et al 2018) which also formed part of a LSST DESC survey strategy white paper for Wide Fast Deep Fields in LSST (Lochner et al 2018). SNANA observation library files (Biswas et al 2017) generated through previous versions of OpSimSummary (and distributed publicly with the SNANA code) have been used in the study of serendipitous detection of Kilonovae (Scolnic et al 2018a) and the LSST DESC Science Requirement Document (The LSST Dark Energy Science Collaboration et al 2018).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Surveys with the characteristics of the low-𝑧 sample require high cadences ( 6 days). Future surveys, such as the LSST, will produce high-quality data with good S/N and cadence (e.g., Lochner et al 2018;Scolnic et al 2018a), overcoming some of the limitations found in this work, thus allowing PISCOLA to produce reliable fits.…”
Section: Effect Of Observational Uncertaintiesmentioning
confidence: 96%